COMUNICAÇÃO, IMAGINÁRIO E IDENTIDADE QUILOMBOLA: A festa de Santo Antônio na comunidade do Mandira em Cananéia-SP - KAWAGUCHI, RENATA CASTRO CARDIAS (2017)
This work is a study on the feast of Santo Antônio in the quilombola community of the Mandira in Cananéia - SP. The research aims to analyze the Feast of Santo Antônio as process of communication to the formation of the social imaginary and the quilombola identity. To this end, some theoretical references will be adopted: The Cultural Studies, The Latin American Thinking and Studies of the Social Imaginary to understand the sociocultural context of the quilombola site refered. It is going to be considered the connections between concepts such as communication, community, citizenship, popular culture, globalization, Identity, imaginary, cultural hybridity and popular religiosity, by the view of the following autors: Raymond Willians, Stuart Hall, Nestor Garcia Canclini, Jesus Martin-Barbero, Luiz Beltrão, José Marques de Melo, Ana Taís Portanova Barros, Magali do Nascimento Cunha, Gilbert Durand, Mircea Elíade, Riolando Azzi, Eduardo Hooarnet and others. The methodology used includes bibliographical, documentary and ethnographic research, with the following techniques: participant observation and interviews with members of the Mandolan quilombola community. This research bring as result that the quilombola, as a declassed population, develops means of communication through folk-communicative expressions from their religious practices, such as the Feast of Santo Antônio, allowing it collectivelly express their feelings and to find protection from social injustices that it suffer constantly.